Risk for the development of Antimicrobial Resistance (AMR) due to feeding of calves with milk containing residues of antibiotics - EFSA Panel on Biological Hazards (BIOHAZ); Antonia Ricci; Ana Allende; Declan Bolton; Marianne Chemaly; Robert Davies; Pablo Salvador Fernández Escámez; Rosina Girones; Kostas Koutsoumanis; Roland Lindqvist; Birgit Nørrung; Lucy Robertson; et al. (EFSA Journal, 2017)
Abstract EFSA was requested to: 1) assess the risk for the development of antimicrobial resistance (AMR) due to feeding on farm of calves with colostrum potentially containing residues of antibiotics; 2) assess the risk for the development of AMR due to feeding on farm of calves with milk of cows treated during lactation with an antibiotic and milked during the withdrawal period, and 3) propose possible options to mitigate the risk for the development of AMR derived from such practices. Treatment of dairy cows during the dry period and during lactation is common in the EU Member States. Penicillins, alone or in combination with aminoglycosides, and cephalosporins are most commonly used. Residue levels of antimicrobials decrease with the length of the dry period. When the interval from the start of the drying‐off treatment until calving is as long as or longer than the minimum specified in the Summary of Product Characteristics of the antimicrobial, faecal shedding of antimicrobial‐resistant bacteria will not increase when calves are fed colostrum from treated cows. Milk from cows receiving antimicrobial treatment during lactation contains substantial residues during the treatment and withdrawal period. Consumption of such milk will lead to increased faecal shedding of antimicrobial‐resistant bacteria by calves. A range of possible options exist for restricting the feeding of such milk to calves, which could be targeting the highest priority critically important antimicrobials. β‐Lactamases can reduce the concentration of β‐lactams which are the most frequently used antimicrobials in milking cows. Options to mitigate the presence of resistant bacteria in raw milk or colostrum are mainly based on thermal inactivation.